Parameter analysis of thermoelectric generator/dc-dc converter system with maximum power point tracking - Twaha, Ssennoga; Zhu, Jie; Li, Bo; Yan, Yuying; Huang, Kuo (Elsevier, 2017)
The power generated from TEG is relatively unstable owing to temperature variations at its hot and cold side terminals. The dc-dc converters can provide more stable power output thereby improving the overall efficiency of TEG system. However, to facilitate better performance improvement, maximum power point tracking (MPPT) algorithm can be applied to extract maximum power from TEG system. Therefore, parameter analysis of a TEG/dc-dc converter system in different modes is being carried out. A TEG-dc-dc boost converter model is analysed in both MPPT and direct pulse width modulation (PWM) modes subjected to a variable load. To further study the capability of dc-dc converters to stabilise the TEG power output, increasing ramp and random hot side temperature is applied to the MPPT and direct PWM based modes so that the effect on output parameters i.e. voltage and power, can be analysed. It is noted that even for the random temperature input to the TEG, the output voltage resulting from the converter is almost constant. Therefore dc-dc converters are able to stabilise the power generated from TEG. It is also observed that dc-dc converter with MPPT based model is able to effectively extract the maximum power without having to adjust any component from the MPPT algorithm as it is the case with direct PWM based model. From the study, it has been established that proper selection of converter components is necessary to reduce converter losses as well interferences on the load connected to TEG-dc-dc converter system.